Pragmatic Markers Used by Saudi Undergraduate EFL Learners in Oral Classroom Presentations at Albaha University - Alzahrani, Saeed Abdullah (International Journal of Linguistics and Translation Studies, 2023)
The current study investigated the use of pragmatic markers during oral classroom presentations by Saudi Arabian undergraduate EFL learners at Albaha University, Saudi Arabia. The use of pragmatic markers in academic contexts such as presentations is significant as failure to use these markers can cause poor comprehension by audience members and instructors who are tasked with grading such work. The method involved categorising and sub-categorising the pragmatic markers used as well as the linguistic meanings and pragmatic functions of these markers. The data were collected using audio recordings of students' oral presentations and were analysed based on Fraser’s (1996) classification and functions of pragmatic markers. A sample (n=20) of Saudi undergraduate EFL learners participated in this study (males: n=10; females: n=10). The results show that in their oral presentations, Saudi EFL undergraduate students tend to use deference and paraphrase markers most frequently, which may reflect Saudi religious and cultural conventions. However, the students’ use of interjections, pausing, and cohesion in their presentations was poor. There is a need to help Saudi Arabian undergraduate EFL learners improve their knowledge and use of pragmatic markers so they can make better oral presentations both at university and in their future careers.